2014
DOI: 10.1001/jamaoto.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment Associated With Depression in US Adults, National Health and Nutrition Examination Survey 2005-2010

Abstract: IMPORTANCE Depression among hearing impaired US adults has not been studied previously. OBJECTIVE To estimate the prevalence of and risk factors for depression among adults with hearing loss. DESIGN, SETTING, AND PARTICIPANTS Adults aged 18 years or older (N = 18 318) who participated in the National Health and Nutrition Examination Survey (NHANES), 2005–2010, a nationally representative sample. INTERVENTIONS Multistage probability sampling of US population. MAIN OUTCOMES AND MEASURES Depression, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
260
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(287 citation statements)
references
References 24 publications
14
260
1
12
Order By: Relevance
“…It is encouraging that psychosocial talk was a focus of one quarter of the history taking phases observed in the current study, given that psychosocial talk is often not a focus of physician-patient interactions in primary health care [14,[30][31][32]. However, given that adults with acquired hearing loss typically attend an audiology appointment because they are experiencing communication difficulties [17,33] and thus may have experienced changes to their lifestyle (e.g., withdrawing from social situations) and/or general well-being [34][35][36][37][38][39], one would expect a greater proportion of audiology appointments to begin with psychosocial interaction.…”
Section: Discussionmentioning
confidence: 91%
“…It is encouraging that psychosocial talk was a focus of one quarter of the history taking phases observed in the current study, given that psychosocial talk is often not a focus of physician-patient interactions in primary health care [14,[30][31][32]. However, given that adults with acquired hearing loss typically attend an audiology appointment because they are experiencing communication difficulties [17,33] and thus may have experienced changes to their lifestyle (e.g., withdrawing from social situations) and/or general well-being [34][35][36][37][38][39], one would expect a greater proportion of audiology appointments to begin with psychosocial interaction.…”
Section: Discussionmentioning
confidence: 91%
“…Hearing loss is independently associated with mortality, 5 poorer cognitive function, 6 -8 incident dementia, 9,10 depression, 11,12 and physical functioning. [13][14][15] The impact of hearing loss on healthy aging translates into significant financial burdens on the health care system.…”
Section: Awareness Of Hearing Loss Manifestations and Implicationsmentioning
confidence: 99%
“…The main consequence of hearing loss is an obvious difficulty in clearly perceiving auditory speech signals. Research has also shown that hearing loss is associated with cognitive decline (Lin et al, 2013;Rönnberg et al, 2011;Wong, Yu, Chan, & Tong, 2014), structural changes in the brain (Boyen, Langers, de Kleine, & van Dijk, 2013;Eckert, Cute, Vaden, Kuchinsky, & Dubno, 2012;Lin et al, 2014;Peelle, Troiani, Grossman, & Wingfield, 2011), mental health problems such as depression (e.g., Li et al, 2014) and social isolation (e.g., Weinstein & Ventry, 1982).…”
Section: Impact Of Hearing Loss On Speech Recognitionmentioning
confidence: 99%